39-4a=7+6(1-5a)

Simple and best practice solution for 39-4a=7+6(1-5a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 39-4a=7+6(1-5a) equation:


Simplifying
39 + -4a = 7 + 6(1 + -5a)
39 + -4a = 7 + (1 * 6 + -5a * 6)
39 + -4a = 7 + (6 + -30a)

Combine like terms: 7 + 6 = 13
39 + -4a = 13 + -30a

Solving
39 + -4a = 13 + -30a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '30a' to each side of the equation.
39 + -4a + 30a = 13 + -30a + 30a

Combine like terms: -4a + 30a = 26a
39 + 26a = 13 + -30a + 30a

Combine like terms: -30a + 30a = 0
39 + 26a = 13 + 0
39 + 26a = 13

Add '-39' to each side of the equation.
39 + -39 + 26a = 13 + -39

Combine like terms: 39 + -39 = 0
0 + 26a = 13 + -39
26a = 13 + -39

Combine like terms: 13 + -39 = -26
26a = -26

Divide each side by '26'.
a = -1

Simplifying
a = -1

See similar equations:

| 2/5h=28 | | Y^4+16y=-1 | | -6x-(-6)-7=-7x+7 | | (-x-9i)(x-9i)=0 | | -38=-18-9 | | F(x)=1n(x-2)-4 | | x(3)+9=27 | | X^2+3=5x(x+6) | | 4(3+m)=8(6m+7) | | (x+9i)(x-9i)=0 | | 4x+7=22-x | | 7z-1=z+22 | | 3v+2y=100 | | 6cosx=4sinx | | (-x-9i)(x+9i)=0 | | -5x-1=29+5x | | -4y+7x=-24 | | 7x-(3+4x)= | | 3a-15=-14 | | 3c+18=14 | | 3r^2+25r+8=0 | | 14x-29=6x+29 | | C=.15M+15 | | 57+66+x=180 | | 1/8logx=-5/3 | | 13-2x=93 | | -5(3x-9)=150 | | 66+x+x=180 | | 1/2X-10=6 | | y^2-8y=20 | | 9x-2=98 | | (-4i)(2i)(-3i)= |

Equations solver categories